Short Communication: Relationship between interferon-tau level (IFN- ?) and embryo mortality incident in Aceh cattle (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Melia J, Siregar TN, Alfahmi L, Husnurrizal, Saumar H, Mukhtar, Meutia N, Panjaitan B, Armansyah T. 2020. Short Communication: Relationship between interferon-tau level (IFN- ?) and embryo mortality incident in Aceh cattle. Biodiversitas 21: 5758-5762. The purpose of this research is to determine the relationship between interferon-tau level (IFN-?) and the incidence of embryo mortality in Aceh cattle from the Province of Aceh, Indonesia. Data were obtained from four Aceh cattle, aged 3-5 years and body weight of 150-250 kg. The cattle were clinically healthy, with at least two regular reproduction cycles, and a pregnant status after estrous synchronization and artificial insemination. This process was carried out on a 10-day interval using the intramuscular administration of prostaglandin F2 alpha (PGF2?) hormone, at a dose of 25 mg, with double injection pattern. The blood samples were collected from the jugular vein on day 14 to 18 post-insemination for the assessment of IFN-? concentration, which was measured using the enzyme linked-immunoassay (ELISA) method and the bovine interferon ELISA kit (Cusabio Technology LLC AII, USA). In addition, the transrectal ultrasonography method was used to test the pregnancy and embryo mortality of the cattle on the 25th day. The examination was repeated every 10 days until day 55. The IFN-? concentrations of pregnant cows against those with embryo mortality on the 14th, 15th, 16th, 17th, and 18th day, were 12.066±8.222 vs 17.853±11.126, 12.983±3.491 vs 20.503±3.858, 12.193±4.535 vs 16.458±8.065, 10.143±5.370 vs 17.604±1.888, and 12.767±7.753 vs 15.096±6.955 pg/mL, respectively. Therefore, the embryo mortality in Aceh cattle is not related to IFN-?.
Keywords: Aceh cattle, IFN-τ, embryo mortality